If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3*x)/5-3 > x/5-7 // - x/5-7
(3*x)/5-(x/5)-3+7 > 0
2/5*x+4 > 0 // - 4
2/5*x > -4 // : 2/5
x > -4/2/5
x > -10
x in (-10:+oo)
(-10:+oo)
| -7.2=1.3n-0.3n-1.0 | | 5(2x+4)+3(2x-2)=24 | | x-.50x=43 | | (y+1)+1=3y | | f-g=3g | | 5(-8b-4)=180 | | 7-(-10+3x)=-238 | | y-(-3)=(8/9)(x-4) | | 2(2-2x)= | | 3x+7=x-21 | | 3x+29-2x+4=-4x | | 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 |